A natureza das ações educativas desenvolvidas por bibliotecárias(os) da Rede Federal de Educação Profissional, Científica e Tecnológica (RFEPCT) - Souza, Ágata Nelza Gomes de (Universidade Federal de São Carlos, 2025)
This study investigates how librarians from the libraries of the Federal Network of Professional Scientific and Technological Education (RFEPCT) and graduates of the professional master’s degree program in Professional and Technological Education (ProfEPT) understand the nature of the educational actions they develop. This is an ontological study that investigates the nature of the entity itself aiming to understand it as a being and the links between its constituent elements. Specifically, we aim to characterize the subjects taking part in the research and their working context; to learn if/how initial training (librarianship) and continuing training(s) contributed to developing the educational actions in question; to identify the typologies and to specify the definitions given to educational actions; to characterize, through the perezhivaniya reported, the constitutive elements of the nature of the educational actions highlighted by the participating subjects; and to identify if/how they understand the presence/relevance of technology in the development of educational actions. We conducted systematic mapping (MS) to identify the content related to the subject and found that most studies on the subject refer to the area of librarianship, with little interlocution with education. This justification for this research is added to others of a social and personal nature. Data collection and analysis are based on the theoretical-methodological framework of Lev Semionovich Vygotsky’s (1896-1934) cultural-historical theory, the category of perezhivanie, as a unit of analysis and analytical reference for part of the data analyzed, mediation as an explanatory principle, and the dialectical approach. The research design is structured based on a quantitative↔qualitative approach by applying a mixed online questionnaire (31 participants, distributed across the five Brazilian regions) and a semi-structured reflective interview (six participants). The results obtained through the questionnaire showed that the group is mostly made up of women who have been working in the RFEPCT for around a decade. We also point out that continuing training, specifically the ProfEPT, is seen as more relevant than initial training in librarianship in terms of contributing to the development of educational actions. In addition, we identified 33 different types of educational actions developed by these subjects, including the development of book clubs/reading clubs, training, workshops, classes, and courses. There is also a marked multidimensionality of definitions attributed to educational actions, which were grouped into six types with clear interrelationships between them. Concerning the interviews, based on the analytical framework developed to analyze the perezhivaniya, five essential elements of these educational actions were identified, namely: work from the perspective of totality, freedom, planning, information mediation, and cultural mediation (intersecting formative character). We also indicate that technological resources are present in the educational activities mentioned and are correlated to the shortage of library workers. Thus, the nature of the educational actions is shown from a systemic, dynamic relationship linked to the principles of professional and technological education (EPT), along with a teleological dimension that expresses a prior and conscious purpose of these professionals, in the face of the invisibility and lack of institutional recognition of their work. We concluded that the educational activities carried out by librarians at the RFEPCT reflect a movement aimed at overcoming the historical dichotomy between the areas of librarianship and education, contributing to the comprehensive training of individuals, following the principles of professional and technological education (EPT), through activities carried out in non-formal educational contexts.

El estudio investiga cómo los bibliotecarios actuantes en las bibliotecas de la Red Federal de Educación Profesional Científica y Tecnológica (RFEPCT) y egresados del máster profesional del Programa de Postgrado en Educación Profesional y Tecnológica (ProfEPT), comprenden la naturaleza de las acciones educativas que desarrollan. Se trata de una investigación ontológica que indaga en la naturaleza del ente y busca comprender su ser y las articulaciones entre sus elementos constituyentes. Se pretende específicamente caracterizar a los sujetos participantes en la investigación y su contexto de acción; identificar si/de qué manera la formación inicial (bibliotecología) y la formación continua contribuyeron al desarrollo de las acciones educativas en cuestión; identificar las tipologías y precisar las definiciones que se dan a las acciones educativas; caracterizar, a través de las perezhivaniya relatadas, los elementos constitutivos de la naturaleza de las acciones educativas evidenciadas por los sujetos participantes; e identificar si comprenden/cómo comprenden la presencia/relevancia de la tecnología en el desarrollo de acciones educativas. Se desarrolló un mapeo sistemático (MS) para indagar los contenidos relacionados a la temática y se identificó el predominio de estudios sobre la temática en el área de bibliotecología, con poco diálogo con la educación. Esta justificación para esta investigación se suma a otras de carácter social y personal. La recolección y análisis de datos se realiza con base en el marco teórico-metodológico de la teoría histórico-cultural de Lev Semionovitch Vygotsky (1896-1934), la categoría perezhivanie como unidad de análisis y marco analítico de parte de los datos analizados, la mediación como principio explicativo y el enfoque dialéctico. El diseño de la investigación se estructura con base en el enfoque cuantitativo↔cualitativo con la aplicación de un cuestionario mixto en línea (31 participantes, distribuidos en las cinco regiones brasileñas) y una entrevista reflexiva semiestructurada (seis participantes). Los resultados obtenidos a través del cuestionario permitieron identificar que el grupo está conformado mayoritariamente por mujeres, con alrededor de una década de experiencia en la RFEPCT. También se destaca que la formación continua, específicamente la ProfEPT, se considera más relevante que la formación inicial en bibliotecología en términos de contribución al desarrollo de acciones educativas. Además, se identificaron 33 diferentes tipos de acciones educativas desarrolladas por estos sujetos, con énfasis en el desarrollo de clubes de lectura, capacitaciones, talleres, clases y cursos. También se observa una marcada multidimensionalidad de las definiciones atribuidas a las acciones educativas. Se agruparon en seis especies con claras interrelaciones entre ellas. En relación a las entrevistas, a partir del marco analítico construido para realizar el análisis de perezhivaniya, se identificaron cinco elementos esenciales de dichas acciones educativas, a saber: trabajar desde la perspectiva de totalidad; libertad; la planificación; mediación informativa; y mediación cultural (carácter formativo intersectado). También se indica que los recursos tecnológicos están presentes en las acciones educativas y se correlacionan con la escasez de personal asignado a las bibliotecas. Así, se clarifica la naturaleza de las acciones educativas a partir de una relación sistémica, dinámica y vinculada a los principios de la educación profesional y tecnológica (EPT), en conjunción con una dimensión teleológica que expresa un propósito previo y consciente de estos profesionales, dada la invisibilidad y falta de reconocimiento institucional de su labor. Se concluye que las acciones educativas desarrolladas por los bibliotecarios de la RFEPCT expresan un movimiento orientado a la superación de la dicotomía histórica entre las áreas de bibliotecología y educación, contribuyendo a la formación integral de sujetos, según los principios de la educación profesional y tecnológica (EPT), a través de acciones realizadas en contextos educativos no formales.
The nature of educational actions developed by librarians of the Federal Network of Professional, Scientific and Technological Education (RFEPCT)
La naturaleza de las acciones educativas desarrolladas por los bibliotecarios de la Red Federal de Educación Profesional, Científica y Tecnológica (RFEPCT)
Keywords: Ação Educativa; Bibliotecário; Vivência; Educação Profissional e Tecnológica (EPT); Rede Federal de Educação Profissional, Científica e Tecnológica (RFEPCT); Educational action; Librarian; Perezhivanie; Professional and Technological Education (EPT); Federal Network of Professional, Scientific and Technological Education (RFEPCT); Acción Educativa; Bibliotecario; Educación Profesional y Tecnológica (EPT); Red Federal de Educación Profesional, Científica y Tecnológica (RFEPCT); CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO